1999
DOI: 10.1128/aem.65.8.3738-3741.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ruminococcus flavefaciens as the Predominant Cellulolytic Bacterial Species of the Equine Cecum

Abstract: Detection and quantification of cellulolytic bacteria with oligonucleotide probes showed that Ruminococcus flavefaciens was the predominant species in the pony and donkey cecum. Fibrobacter succinogenes and Ruminococcus albus were present at low levels. Four isolates, morphologically resembling R. flavefaciens, differed from ruminal strains by their carbohydrate utilization and their end products of cellobiose fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
6
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 21 publications
8
77
6
5
Order By: Relevance
“…Di¡erences in results between hybridisation studies and PCR-generated libraries of intestinal micro£ora could be indicative of a high degree of PCR bias, favouring particular groups of sequences over others, thus giving rise to the apparent contradictions between PCR and hybridisation data. This particularly applies to the detection of Fibrobacter rRNA in the horses sampled here (up to 9.4%), which, in agreement with other studies that have used the Fib225 probe for quantifying Fibrobacter in equine gut [31,56], con¢rms the ¢ndings of Tajima et al [23] that biases associated with PCR are responsible for the non-detection of Fibrobacter in PCR-based studies of microbial diversity in equine and ruminal systems where this group may be expected to thrive [12,16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Di¡erences in results between hybridisation studies and PCR-generated libraries of intestinal micro£ora could be indicative of a high degree of PCR bias, favouring particular groups of sequences over others, thus giving rise to the apparent contradictions between PCR and hybridisation data. This particularly applies to the detection of Fibrobacter rRNA in the horses sampled here (up to 9.4%), which, in agreement with other studies that have used the Fib225 probe for quantifying Fibrobacter in equine gut [31,56], con¢rms the ¢ndings of Tajima et al [23] that biases associated with PCR are responsible for the non-detection of Fibrobacter in PCR-based studies of microbial diversity in equine and ruminal systems where this group may be expected to thrive [12,16,17].…”
Section: Discussionsupporting
confidence: 92%
“…2). The apparent di¡erences between our study and those mentioned above [7,8] could be as a result of an unknown PCR bias or perhaps di¡erences in diet resulting in low abundance of F. succinogenes and R. £avefaciens. Tajima et al [11,12] also failed to detect F. succinogenes in two separate 16S rRNA studies on the rumen.…”
Section: Discussioncontrasting
confidence: 62%
“…in the equine caecum and colon by oligonucleotide probing and concluded that Fibrobacter succinogenes accounted for up to 12% of total rRNA extracted from the caecum and 4% from the colon. Similarly, Julliand et al [7] detected F. succinogenes, R. £avefaciens and Ruminococcus albus in equine caecum by oligonucleotide probing, but concluded that R. £avefaciens was the predominant cellulolytic species in the caecum (up to 9% of total rRNA). Interestingly, in our study we did not recover any sequences at all relating to F. succinogenes or R. albus, although we did recover three sequences that formed a single OTU with R. £avefaciens (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were cultured in Petri plates on Rogosa agar 5 and on a bile-esculin-azide agar medium (BK158HA 5 ), respectively. Cellulolytic bacteria were counted on a modified broth medium containing filter paper as the sole cellulolytic substrate (Halliwell and Bryant 1963;Baruc et al 1983;Julliand et al 1999). The concentration of cellulolytic bacteria was taken as the most probable number of Mac Grady (Hughes and Plantat 1983).…”
Section: Measurements and Analytical Methodsmentioning
confidence: 99%